SimPhospho: a software tool enabling confident phosphosite assignment - Veronika Suni; Tomi Suomi; Tomoya Tsubosaka; Susumu Y. Imanishi; Laura L. Elo; Garry L. Corthals (OXFORD UNIV PRESS, 2022)
Motivation: Mass spectrometry combined with enrichment strategies for phosphorylated peptides has been successfully employed for two decades to identify sites of phosphorylation. However, unambiguous phosphosite assignment is considered challenging. Given that site-specific phosphorylation events function as different molecular switches, validation of phosphorylation sites is of utmost importance. In our earlier study we developed a method based on simulated phospho-peptide spectral libraries, which enables highly sensitive and accurate phosphosite assignments. To promote more widespread use of this method, we here introduce a software implementation with improved usability and performance.Results: We present SimPhospho, a fast and user-friendly tool for accurate simulation of phospho-peptide tandem mass spectra. Simulated phosphopeptide spectral libraries are used to validate and supplement database search results, with a goal to improve reliable phosphoproteome identification and reporting. The presented program can be easily used together with the TransProteomic Pipeline and integrated in a phosphoproteomics data analysis workflow.Availability and implementation: SimPhospho is open source and it is available for Windows, Linux and Mac operating systems. The software and its user's manual with detailed description of data analysis as well as test data can be found at https://sourceforge.net/projects/simphospho/.Contact: veronika.suni@utu.fi or G.L. Corthals@uva.nlSupplementary information: Supplementary data are available at Bioinformatics online.